RELATIONSHIP OF FAMILY MOTIVATION AND THE HEALTH OFFICERS' ROLES WITH MOTHER'S BEHAVIOR IN GIVING VITAMIN A TO TODDLER (CASE STUDY IN THE TEGAL ARUM HEALTH CENTER TEBO DISTRICT, JAMBI PROVINCE) - Sari, Puspita; Sayuti, Solihin; Rozalia (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACT Background: Vitamin A is an indispensable nutrient for humans and very important in physiological processes of the body, including cell growth, improving visual function, improving immunology and body growth. Giving high dose of vitamin A for infants, toddlers and postpartum mothers could decrease morbidity and mortality of infants and toddlers. The percentage of Tegal Arum Public Health Center in giving Vitamin A to toddlers was low (37,30%) while the target indicator was 100%.Objective: This study aims to determine the description and relationship of family motivation and the role of officers with maternal behavior in vitamin A in toddlers in the Tegal Arum public Health Center, Tebo Regency, Jambi Province.. Methods: This research was a quantitative study with a cross-sectional design, using proportional random sampling. In this study, the samples were mothers who had toddlers in the working area of